Applying formative assessment strategies in the teaching of poetry: An experiment with third-year English studies students at the University of Limpopo - Nkealah, N.E. (South African Journal of Higher Education, 2019)
Formative assessment is fundamental to effective teaching and learning. Positioning itself within a discourse that recognises the value of formative assessment in higher education, this article reports on an experiment conducted with third-year English Studies students at the University of Limpopo in which a formative task was designed and administered to students in a poetry class. A feedback system was then established through which students were able to get comments to help them improve their essays on poetry. Final essays were then graded following an assessment rubric designed and disseminated to students. The results indicate that the practical implementation of formative assessment strategies led to students achieving high academic performance and acquiring lifelong skills. Effectively, the innovative application of formative assessment in teaching has the potential to boost transformation in Higher Education Institutions.